1997
DOI: 10.1111/j.1525-1470.1997.tb00218.x
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Bloom Syndrome with Conjunctival Telangiectasia

Abstract: Bloom syndrome is a rare genodermatosis characterized by photosensitivity, telangiectasias, growth retardation and malignancies. Eye findings have rarely been mentioned in case reports of this syndrome. We report a child with Bloom syndrome who had pronounced bulbar conjunctival telangiectasia originally diagnosed as episcleritis. Bulbar telangiectasia are frequently described in other genodermatoses such as ataxia telangiectasia and hereditary hemorrhagic telangiectasia, but are infrequently noted in Bloom sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Moreover, she had prominent bulbar conjunctival telangiectasia which is a rare feature among these patients. Only six of the 165 patients in the Bloom syndrome registry possessed this feature (1), and one recently reported patient had presented with symptomatic bulbar conjunctival telangiectasia (16).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, she had prominent bulbar conjunctival telangiectasia which is a rare feature among these patients. Only six of the 165 patients in the Bloom syndrome registry possessed this feature (1), and one recently reported patient had presented with symptomatic bulbar conjunctival telangiectasia (16).…”
Section: Discussionmentioning
confidence: 99%
“…Retinoblastoma has been reported in a child 17 ; an infant with bilateral optic nerve hypoplasia has also been reported. 15 In conclusion, the collected observations in Bloom syndrome indicate that a wide variety of ocular abnormalities can arise as a consequence of excessive somatic mutations. While reports of retinal abnormalities have been scant in this disorder, the ophthalmological spectrum of Bloom syndrome can be expanded from the multiple, independent findings in this patient.…”
Section: Discussionmentioning
confidence: 91%
“…Early onset of retinal drusen is the most frequent finding, and drusen are typically described as small, hard and nonconfluent [Bhisitikul and Rizen, 2004;Cefle et al, 2007]. Other, more rarely reported ophthalmologic abnormalities include nonproliferative diabetic retinopathy and leukemic retinopathy in a single individual [Bhisitikul and Rizen, 2004] as well as conjunctival telangiectasia and optic nerve hypoplasia [Sahn et al, 1997]. Gibbons et al [1995] reported a single case of retinoblastoma in a 2-year-old with suspected BS.…”
Section: Dermatologic Manifestationsmentioning
confidence: 99%